Strategic Financial Planning Analysis to Deliver Sustainable Profits - Yenny Rany; Rhian Indradewa; Ferryal Abadi; Unggul Kustiawan (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The evolution of consumer behavior in Indonesia, along with technological advancements, has led to a growing demand for personal shopping services, particularly in major cities. The digital application TITIP provides a digital platform solution that makes it easy for users to obtain necessary items without having to travel to get the needed goods. With a comprehensive investment analysis of market conditions and competitors, TITIP can determine financial planning strategies that can enhance market development growth, increase brand awareness, and implement digital marketing to strengthen TITIP's position in the digital consignment service industry. This research uses qualitative descriptive methods and data analysis on financial planning, which includes a framework of short-term, medium-term, and long-term financial goals; revenue and cost management strategies; and five-year financial projections. The results of the business feasibility analysis show strong growth potential and significant opportunities for the TITIP application to become the leading consignment service platform in Indonesia. Financial planning using investment feasibility analysis calculations such as Net Present Value (NPV), Payback Period (PP), and Internal Rate of Return (IRR), this study assesses TITIP's ability to optimize investments and achieve maximum profit growth. The results show that TITIP has a strong financial base, enabling operational efficiency and creating sustainable growth.